Pengaruh Bauran Promosi dan Kualitas Produk terhadap Keputusan Pembelian pada Marketplace Shopee dalam Perspektif Islam - Siti Sopuroh; Hendri Tanjung (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
In the era of digitalization, the development of information and technology is increasing so that we cannot deny the rapid developments in the trade sector. So that the emergence of online trading competition in various markets. E-commerce players must be able to take the initiative to be able to compete, especially in the quality of products offered to consumers, which greatly influences consumer buying interest, good product quality in terms of performance, durability, benefits and others. besides that, the peak of success of a company's progress is in terms of promotions that must be carried out to attract more consumer buying interest. In carrying out promotions to get attention, there are four indicators that are carried out, namely: advertising, sales promotion, publication, and personal selling. As done by the Shopee marketplace, it is very attractive to consumers so that it becomes a marketplace that is in great demand. The purpose of this research is to find out whether there is an effect of the promotion mix and product quality if it is done simultaneously. Meanwhile, in conducting this research, the quantitative method is used, where the data is collected by distributing questionnaires to students at the Ibn Khaldun University, Bogor. The tool used in processing the data is the SPSS 26 application program. The results show that the promotion mix affects purchasing decisions by looking at t-count > t-table looking at the significance value on X1 which is 0.000 <0.05 and the t-count value > t -table (3,568 > 1,984). Meanwhile, product quality has an effect on purchasing decisions with a significance value of 0.000 <0.05, and a t-count value (3.950) > t-table (1.984). Promotional mix and product quality have an effect on purchasing decisions, while in statements such as honesty in promotions it is still minimal so it needs to be improved again. Keywords: Promotional mix, product quality, purchasing decisions